A failure of ambition on climate action will amplify humanitarian needs: humanitarian actors are struggling to keep up with the demands of increasingly frequent, erratic, and overlapping crises at current levels of warming - Voûte, Caroline; Guevara, Maria; Schwerdtle, Patricia (The BMJ, 2021)
Humanitarian actors are struggling to keep up with the demands of increasingly frequent, erratic, and overlapping crises at current levels of warming
Gesehen am 15.02.2022